MEAT COMSUMPTION RATE AND ITS ECONOMY IN MEGHALAYA - MARNGAR, D.; WANSWETT, I. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2013)
The Meghalayan food comprises of rice along with fish or meat preparations. In fact, rice is the staple food of the people of Meghalaya. About 80 - 85 % of the total human population in Meghalaya consumes meat. There is a huge demand of cattle in the state; thus, animals form a part of village economy for meat, milk and to a lesser extent manure. There is lot of scopes for the rural people of Meghalaya in cattle farming, piggery, and poultry to produce these animals and meet the demands in the markets in the state. This business would help rural people from unemployment, eradicate poverty, increase rural economy aid also increase the economy of the state as a whole.